SURGEON TECHNIQUES IN NON-FEMTOSECOND LASER-ASSISTED CATARACT SURGERY (TECHNOFLACS) QUESTIONNAIRE: FACE AND CONTENT VALIDATION - Md-Muziman-Syah, Md Mustafa; Azman, Ahmad Amiruddin; Hakim Zamzuri, Muhammad Faiz; Ab. Halim , Noorhazayti; Marzuki , Nazaryna; Mohd Kamal, Khairidzan (International Journal of Allied Health Sciences, 2021)
Background: Surgeon techniques during cataract surgery is one of the major factors that influence the magnitude and axis of surgically induced astigmatism. Nevertheless, no validated instrument is readily available in documenting the necessary information on surgeon techniques in non-femtosecond laser-assisted cataract surgery (NoFLACS). The purpose of this study was to validate the Surgeon Techniques in Non-Femtosecond Laser-Assisted Cataract Surgery questionnaire (TechNoFLACS) Methodology: Fifteen questionnaire items were developed based on peer-reviewed literatures that included domains related to the surgeon techniques in NoFLACS. Ten subject-matter experts (SMEs) were involved in face and content validations using qualitative and Lawshe’s methods, respectively. The items were modified based on comments and suggestions from the SMEs. Content validation ratio (CVR) for each item was calculated. Items that did not achieve CVR value of 1 were removed and final content validity index (CVI) of the TechNoFLACs was obtained. Results: Of the 15 items, six items with a CVR of less than 1 were removed (items number: 1, 8, 9, 11,12, 15). The CVI before the items removal was 0.61. After the modification, nine items remained and the final CVI was 1. Conclusion: The TechNoFLACS is a valid and reliable tool for documenting the relevant information on surgeon techniques during NoFLACS. Therefore, the TechNoFLACS may useful for research related to surgeon techniques. Keywords: surgeon technique, Non-femtosecond laser-assisted cataract surgery, face validation, content validation, questionnaire